Social perception as a determine factor in the risk management in Costa Rica: Reflexional lines around the experience from the university extension - Vargas Loáiciga , Carlos (2022)
Costa Rica is one of the countryies most prone to emergency situations due to natural events. The location and geographic conditions are determinant so that their degree of vulnerability is considerably high. In the last thirty years, there have been a series of emergencies that have claimed lives, as well as a high economic impact, such as the Cinchona Earthquake (2009), Hurricane Otto (2016) and Tropical Storm Nate (2017), experiences that marked the country considerably. Taking into account this event, the Universidad Técnica Nacional, through the University Community Work, has generated participation processes that try to promote the culture of prevention. Therefore, this article is a systematization of the experience in which we worked with the community of San Vicente to strengthen the culture of prevention, based on stories and actions carried out, allowing reflection from the university extension.